Ø§ÙÙØ³Ø·ÙØ© Ø¥Ø²Ø§Ø¡ Ø§ÙØ±Ø§Ø¯ÙÙØ§ÙÙØ© ÙÙ Ø§ÙØ¥Ø³ÙØ§Ù: Ø§ÙØ³ÙÙÙ Ø§ÙØ³ÙØ§Ø³Ù ÙØ·Ø§Ø¦ÙØ© Ø±Ø§Ø¯ÙÙØ§ÙÙØ© ÙÙ Ø§ÙÙØ³ÙÙÙÙ ÙÙ Ø¹ÙØ¯ ØÙÙÙØ© Ø±Ø¦ÙØ³ Ø§ÙØ¬ÙÙÙØ±ÙØ© Ø§ÙØ¥ÙØ¯ÙÙÙØ³ÙØ© Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ ÙØ§ØØ¯ - Hamim, Thoha (JOURNAL OF INDONESIAN ISLAM, 2007)
This article offers a brief account of the political turmoil which led to the abdication of President Abdurrahman Wahid. President Wahid faced serious challenges, particularly from his traditional opponents, the Muslim militants. They made efforts to deligitimize his government using street protests, provocative talk shows and writings which enabled them to create political unrest during Wahidâs short-lived governÂment. The Muslim militants eventually thought that Wahid did not deserve political support from the Muslim community due to his controversial views. The political feud between Wahid and the militants actually is not as simple as it appears. The two belong to different âreligious schools of thoughtâ; the former represents contextual ways of thought, and the latter supports textual mindsets. While the first opens a space to dialogue between texts and contexts, the latter follows a one-way path, applying literally what has been stated in the prophetic and scriptural texts.